A DFT+U approach: Superior charge transfer characteristics and optoelectronic properties of GQD@TiO2 rutile (110) surface for improved hydrogen evolution - Ullah, F. (Elsevier B.V., 2022)
The understanding on complex electronic structure and charge transfer characteristics is crucial in the development of heterostructure-based photocatalyst such as graphene quantum dots (GQD) and titanium dioxide (TiO2). Simulation studies will be useful in gaining valuable insight on the complex system at atomistic level. Herein, for the first time, a theoretically designed heterogeneous GQD modified TiO2 (110) interface model using Hubbard's modified first-principles density functional theory (DFT+U) is presented. The structural properties were simulated with PerdewâBurkeâErnzerhof assisted generalized gradient approximation (GGA+PBE) and optoelectronic properties with Hubbard's modified (GGA+U) exchange correlation functional. The addition of GQD reduces the bandgap energy of the TiO2 rutile (110) surface from 2.95 eV to 1.86 eV, thereby improving the visible light response as it reduces the electron transition energy. Charge density difference map and Mulliken population analysis demonstrate frequent transfer of charges from GQD to the TiO2 surface, resulting in reduction of charge recombination rate. Moreover, the energy band edge estimation confirms a suitable band edge position in accordance with the redox potential of water. The collective effect of the heightened absorption of visible light and effective charge separation led to a significant photocatalytic performance of the hybrid photocatalyst. Â© 2022 Elsevier B.V.